2020
DOI: 10.18203/issn.2454-2156.intjscirep20205492
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of magnitude and factors affecting outcomes of head injury at Addis Ababa burn emergency and trauma hospital, Ethiopia

Abstract: <p class="abstract"><strong>Background:</strong> Head injury is the leading cause of death and disability worldwide and has become one of the highest community health problems worldwide including Ethiopia. This study aims to assess the magnitude and factors affecting the outcome of head injury patients at Addis Ababa burn and emergency treatment Hospital from 01 January 2018 to 31 December 2019.</p><p class="abstract"><strong>Methods:</strong> A retrospective review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…6,7 The TBI is particularly frequent in younger people, 4 and Ethiopia has more than 70 million citizens younger than 30 years of age. 8 The prevalence of TBI in Ethiopia is reported as 29-40% [9][10][11] and a study done at the University of Gondar Specialized Hospital showed that the prevalence of TBI was reported as 40.5%. 11 Differences in patient characteristics, socioeconomic status, ICU admission thresholds, health-care systems, and the availability of varying numbers of ICU beds among hospitals had shown to be the causes for the variation across different continents.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The TBI is particularly frequent in younger people, 4 and Ethiopia has more than 70 million citizens younger than 30 years of age. 8 The prevalence of TBI in Ethiopia is reported as 29-40% [9][10][11] and a study done at the University of Gondar Specialized Hospital showed that the prevalence of TBI was reported as 40.5%. 11 Differences in patient characteristics, socioeconomic status, ICU admission thresholds, health-care systems, and the availability of varying numbers of ICU beds among hospitals had shown to be the causes for the variation across different continents.…”
Section: Introductionmentioning
confidence: 99%